Analysis the Performance of Silicon Solar Cell Parameters with the Ambient Temperature using Fuzzy Logic (Journal of the College of Basic Education, 2023)
In this paper, the fuzzy logic technique is used to obtain the optimal value for the main parameters of silicon solar cell in different temperatures. The important parameters to perform the solar cell is, short circuit current (Isc), open circuit voltage (Voc), fill factor (F.F) and efficiency (ηm). The experimental results for this method show to obtain on the maximum value of conversion efficiency when the values of T is low , Isc is high , Voc is low ,Pin is low, Temp is low Then Im is high, Vm is low, Pm is high, F.F is high, Eff. is high &Rcell is low.